Advances of flexible pressure sensors toward artificial intelligence and health care applications. Issue 2 (17th October 2014) - Zang, Yaping; Zhang, Fengjiao; Di, Chong-an; Zhu, Daoben
Abstract : Incorporating flexible pressure sensors with organic electronic devices allows their promising applications in artificial intelligence and the health care industry. Abstract : By virtue of their wide applications in personal electronic devices and industrial monitoring, pressure sensors are attractive candidates for promoting the advancement of science and technology in modern society. Flexible pressure sensors based on organic materials, which combine unique advantages of flexibility and low-cost, have emerged as a highly active field due to their promising applications in artificial intelligence systems and wearable health care devices. In this review, we focus on the fundamentals of flexible pressure sensors, and subsequently on several critical concepts for the exploration of functional materials and optimization of sensing devices toward practical applications. Perspectives on self-powered, transparent and implantable pressure sensing devices are also examined to highlight the development directions in this exciting research field.